ANTIHYPERTENSIVE ACTIVITY OF BAMBOO SHOOT: A REVIEW - O, JIMMY DEVI; Pamba, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Bamboo shoots contain various protein, carbohydrates, amino acids, minerals, fat, sugar, fiber, and inorganic salts. They contain 17 amino acids, 8 of which are essential for the human body. Tyrosine amounts to 57-67% of the total amino acid content. Aqueous extracts of bamboo shoot were found to contain bamboo shoot angiotensin converting enzyme inhibitory peptide (bamboo shoot peptide [BSP]) fraction. On identification of the fraction, Asp-Tyr was found as the key active component. It reduces systolic blood pressure. The phenolic compound present in BSP is having vasodilatory effect, which can decrease hypertension. Keywords: Bamboo extract, Antihypertensive, Bamboo shoot peptide, Angiotensin converting enzyme inhibitor.